2015
DOI: 10.1152/ajpheart.00153.2015
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor as a multifunctional regulator of wound healing

Abstract: Wietecha MS, Król MJ, Michalczyk ER, Chen L, Gettins PG, DiPietro LA. Pigment epithelium-derived factor as a multifunctional regulator of wound healing. Am J Physiol Heart Circ Physiol 309: H812-H826, 2015. First published July 10, 2015; doi:10.1152/ajpheart.00153.2015.-During dermal wound repair, hypoxia-driven proliferation results in dense but highly permeable, disorganized microvascular networks, similar to those in solid tumors. Concurrently, activated dermal fibroblasts generate an angiopermissive, provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 66 publications
2
72
0
Order By: Relevance
“…Recent research demonstrated that skin wounds healed normally despite reduced angiogenesis [57,58]. This observation is further supported by the fact that wounds in fetal skin and the oral mucosa heal without scarring despite less angiogenesis compared with adult skin [57,59].…”
Section: Angiogenesis In Skin Wound Healingmentioning
confidence: 97%
“…Recent research demonstrated that skin wounds healed normally despite reduced angiogenesis [57,58]. This observation is further supported by the fact that wounds in fetal skin and the oral mucosa heal without scarring despite less angiogenesis compared with adult skin [57,59].…”
Section: Angiogenesis In Skin Wound Healingmentioning
confidence: 97%
“…A CD31 antibody has frequently been used to stain endothelial cells. 11,21,24,25 In this study, the results of paired measurements obtained from 2D ultrasound images with the Color Doppler mode and immunohistologically stained sections on day 14 after wounding showed that Pearson's correlation coefficients were r=0.927, 0.871, 0.717, and 0.913 for wounds 1, 2, 3, and 4, respectively, indicating a correlation. This result showed that a strong correlation for % vascularity was obtained between paired 2D ultrasound imaging with the Color Doppler mode and sections immunohistologically stained for the anti-CD31 antibody.…”
Section: Discussionmentioning
confidence: 53%
“…Eight-week old-female C57BL/6 mice (Harlan Laboratories, Inc., Indianapolis, IN) were subjected to standardized skin wounds 12 as previously described. Briefly, mice were anesthetized with ketamine (100 mg/kg) and xylazine (5 mg/kg), and two 3-mm-diameter full-thickness excisional wounds were made on the shaved dorsal skin using a biopsy punch (Acuderm, Inc., Ft. Lauderdale, FL).…”
Section: Animal Modelmentioning
confidence: 99%
“…Topical recombinant PEDF (rPEDF) treatment was applied daily to each wound until day 10 postinjury as described in our previous study. 12 For the first 3 days, 2 lg of rPEDF in 10 lL 25% pluronic gel (Sigma-Aldrich, St. Louis, MO) was directly applied to the surface of each wound. From day 4 to 10, 2 lg rPEDF in 10 lL phosphate-buffered saline (PBS) was injected intradermally into each wound.…”
Section: Pedf Treatmentmentioning
confidence: 99%
See 1 more Smart Citation